The survival of librarian in new era / Fatin Syahirah Pawzi and Nor Ashikin Ngadiron - Pawzi, Fatin Syahirah; Ngadiron, Nor Ashikin (Faculty of Information Management, 2015)
Librarian is always being a reference to the user. However, things change and the development of technology in the new era might change the perception of the community towards librarian. In this article, we are discussing how the librarian can survive in the future and what is the best effort or strategy for the librarian to survive in the new era.